The relationship between Information Technology (IT) resources and employee’s job perfomance at Politeknik Melaka / Nor Anis Mat Aris - Mat Aris, Nor Anis (Faculty of Business and Management, 2014)
This study is carried out to identify the level of employee's job performance affected by information technology (IT) resources at Politeknik Melaka and at the same time to identify whether there is correlation between information technology (IT) resources and employee's job performance. The final objective of this study is to investigate which information technology (IT) resources has a greater influence on employee's job performance. In getting relevant data, 86 samples of questionnaires were distributed to all level of employee's management at each department or units at Politeknik Melaka. Data collected were analyzed by using Statistical Package for Social Science (SPSS) program. The analysis includes frequency, reliability, mean and standard deviation as well as correlation analysis. The study showed that the level of employee's job performance determined by existence of information technology (IT) resources at Politeknik Melaka. All of the independent variables in the study (IT infrastructure, IT application and IT knowledge) are significant toward employee's job performance. There was moderate relationship between information technology (IT) infrastructures and employees job performance. Information technology (IT) application relationship toward employee's job performance resulted stronger correlation. Information technology (IT) had a greatest correlation with employee's job performance rather than other variables in this study. Thus, (IT) knowledge gives greatest contribution toward employee's job performance at Politeknik Melaka.